Index cards - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Interested in developing your own (organisation's) library and looking for more contacts? Here are three excellent ports of call to drop in on.The International Association of Agricultural Information Specialists (IAALD) is a loose and open...